Water quality and potamoplankton periodicity of Sitalakhsya river, Narayanganj, Bangladesh - Hossain Bhuiyan, Mohammad Azmal; Islam, Md Rasikul; Islam, SAM Shariar; Kowser, Abu; Kakoly, Shahina Akter; Mohid, Mahin; Islam, Saiful; Khondker, Moniruzzaman (Dhaka University Journal of Biological Sciences, 2022)
The section of Sitalakhsya River near heavily industrial zone of the District of Narayanganj has been studied for its water quality and potamoplankton dynamics. One year bimonthly sampling from DakhshinRupshi Station of the river was carried out. The air and water temperature of the river ranged from 25.6 - 34.0°C and 26.5 - 32.8°C, respectively. The temperature of water was lower than air by ca. 2.0°C. Water depth at the study station did not vary much but fluctuated only between 6.09 and 7.92 m. The Secchi disc transparency (Zs) varied from 0.2 - 0.6 m showing the lowest in March. Total dissolved Solids (TDS) load in water was 85 - 663 mg/l but the electrical conductivity varied from 110 - 910 μS/cm being the month of March as highest record. pH was alkaline and the fluctuations were negligible (7.2 - 7.4). Alkalinity peaked in March (6.65 meq/l) which dropped to 1.00 meq/l in August and October. Both dissolved oxygen (DO) and free carbon dioxide levels were low which varied from 0.37 - 2.43 and 0.04 - 1.93 mg/l, respectively. Among dissolved nutrients, soluble reactive phosphorus (SRP) showed a low value from May to December (89.48 - 127.70 μg/l). It, however, peaked during March (1265.94 μg/l). Soluble reactive silicate (SRS) concentration ranged from 7.01 - 82.11 mg/l, while the concentration of NO3-N ranged from 0.19 - 1.29 mg/l. The potamoplankton biomass as chl-a ranged from 3.38 - 24.52 μg/l, while its degraded product phaeopigment varied from 1.97 - 11.13 μg/l. The total density of potamoplankton showed their highest growth during December to March (2223 - 4293 ×103) and the lowest from May to October (181 - 785 ×103). The ranges of water quality and planktonic parameters recorded from the Sitalakhsya River are quite comparable with three other peripheral rivers of Dhaka Metropolitan City (DMC) namely, Balu, Turag, and Buriganga. But, low DO and poor transparency along with higher load of TDS made this river water quality relatively lower grading compared to others. Dhaka Univ. J. Biol. Sci. 30(3 CSI): 487-497, 2022 (June)